The Indo-European Origin of Albanian Arboreal Collectives Ending with -íshtë - Witczak, Krzysztof Tomasz (Zeitschrift für Balkanologie, 2005)
The Albanian collectives ending with -íshtë (and also -shtë) are the most numerous and they create a productive formation. They refer usually (if not exclusively) to a gathering of trees (or plants) and designate ‘a field in which a certain kind of vegetation, plant or tree, grows’. The present author suggests that the Albanian collectives in question are not an innovative formation, but an archaism of Indo-European origin. They derive securily from the Indo-European collective formations ending with *-istos or *-istōn. The related collectives are also attested in Greek, Hittite, Celtic, Germanic and Slavic.